Pengaruh Brand Awareness, Brand Image, dan Kualitas Produk terhadap Keputusan Pembeli Sandal Havaianas di Jakarta Pusat - Euis Paramita; Darkiman Ruminta; Dudi Duta Akbar (MANAJEMEN, 2025)
The increasingly dynamic global business competition requires companies, including those in the fashion industry, to continuously innovate by offering products that are not only functional but also reflect consumers’ lifestyles, such as sandals that have become part of brand identity and personal trends among younger generations. Havaianas, as one of the leading sandal brands, has successfully maintained its global presence since 1962 through design innovation, international market reach, and strong brand power supported by Alpargatas S.A. This study aims to analyze the influence of Brand Awareness, Brand Image, and Product Quality on consumer Purchase Decisions of Havaianas sandals in Central Jakarta. A quantitative approach was employed using a survey method and questionnaire as the research instrument. A sample of 384 respondents was selected using accidental sampling. Data were analyzed using multiple linear regression with SPSS software. The results indicate that Brand Awareness, Brand Image, and Product Quality have both partial and simultaneous positive and significant effects on Purchase Decisions. These findings suggest that all three variables play a crucial role in shaping consumer preferences for Havaianas sandals. Therefore, it is recommended that the company strengthen Brand Awareness, build a positive Brand Image, and maintain consistent product quality to enhance consumer purchasing decisions.